Melt layer macroscopic erosion of tungsten and other metals under plasma heat loads simulating ITER off-normal events - Garkusha, I.E.; Bandura, A.N.; Byrka, O.V.; Chebotarev, V.V.; Garkusha, V.V.; Kulik, N.V.; Makhlaj, V.A.; Solyakov, D.G.; Stal’tsov, V.V.; Tereshin, V.I.; Landman, I.; Wuerz, H. (Вопросы атомной науки и техники, 2002)
This paper is focused on experimental analysis of melt layer erosion and droplet splashing of tungsten and other metals under heat loads typical for ITER FEAT off-normal events, such as disruptions and VDE’s. Plasma pressure gradient action on melt layer results in erosion crater formation with mountains of displaced material at the crater edge. It is shown that macroscopic motion of melt layer and surface cracking are the main factors responsible for tungsten damage. Weight loss measurements of all exposed materials demonstrate inessential contribution of evaporation process to metals erosion.